Environmental quality: impact of economic growth. (October 2015) - Bansal, Sangeeta
Abstract Using a vertically differentiated product model, the paper aims to investigate the effects of economic growth on market provision of product quality. The quality attribute considered is the environmental friendliness of products. Economic growth is modeled as a shift in income distribution. It shows that the effect of economic growth depends on the form it takes. A growth in income that is uniform across consumers improves the cleanup levels adopted by both firms. However, a growth in income that is accompanied by changes in income inequality may result in the lowering of one of the two qualities. More specifically, if the growth in income is accompanied by increased disparities in income distribution, the quality of the (environmentally) inferior variant is reduced. This has serious implications for the poor consumers if the product has safety or health hazards. The paper suggests a regulatory measure to prevent such deterioration in the quality of the inferior variant.